The enchantress - Scott, Michael, 1959- (New York : Delacorte Press, 2012)
"The twins of prophecy have been split. Nicholas Flamel is near death. John Dee has the swords of power. And Danu Talis has yet to fall. The future of the human race lies in the balance--how will the legend end?"--Provided by publisher.
Keywords: Flamel, Nicolas, -- d. 1418 -- Juvenile fiction; Dee, John, -- 1527-1608 -- Juvenile fiction; Flamel, Nicolas, -- d. 1418 -- Fiction; Dee, John, -- 1527-1608 -- Fiction; Alchemists -- Fiction; Magic -- Fiction; Supernatural -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction